Organizational and Tactical Issues of Temporary Access to Things and Documents During the Investigation of Criminal Bankruptcy - Marushev, A. D. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article is devoted to the problem of application of temporary access to things and documents as a measure of criminal proceedings in the investigation of criminal bankruptcy. Formulated and proposed the actual basis for the use of temporary access to things and documents in the investigation of criminal bankruptcy. Possible accounting documents subject to seizure by applying temporary access to things and documents in crimes of this category are highlighted.